Destination’s efforts and commitment towards recycling - Japutra, A.; Loureiro, S. M. C. (Current Issues in Tourism, 2020)
This study examines how a destination can play a role in creating tourists’ positive emotions during their visit to enhance affective commitment to recycle beyond their visit. Based on a modified Theory of Planned Behaviour, destination’s efforts (subjective norms, perceived behavioural control and situational control, and personal norms) during tourists visit in the destination are used to explain positive emotions to recycle in the destination. These positive emotions, in turn, will develop affective commitment to recycling in general. In addition, this study also examines the moderating role of personal values (i.e. self-transcendence values) in strengthening tourists’ commitment to recycle. The conceptual framework was tested based on a survey of 523 tourists in the International Humberto Delgado Airport of Lisbon, Portugal. The results show support that destination’s efforts could develop tourists’ positive emotions to recycle in the destination and affective commitment to recycle in general. The results also suggest that self-transcendence values will bolster tourists’ commitment to recycle.